Frontier Molecular Orbital Contributions to Chlorination versus Hydroxylation Selectivity in the Non-Heme Iron Halogenase SyrB2 - Srnec, Martin; Solomon, Edward I (Journal of the American Chemical Society, 2017)
The ability of an FeIV═O intermediate in SyrB2 to perform chlorination versus hydroxylation was computationally evaluated for different substrates that had been studied experimentally. The π-trajectory for H atom abstraction (FeIV═O oriented perpendicular to the C-H bond of substrate) was found to lead to the S = 2 five-coordinate HO-FeIII-Cl complex with the C• of the substrate, π-oriented relative to both the Cl- and the OH- ligands. From this ferric intermediate, hydroxylation is thermodynamically favored, but chlorination is intrinsically more reactive due to the energy splitting between two key redox-active dπ* frontier molecular orbitals (FMOs). The splitting is determined by the differential ligand field effect of Cl- versus OH- on the Fe center. This makes chlorination effectively competitive with hydroxylation. Chlorination versus hydroxylation selectivity is then determined by the orientation of the substrate with respect to the HO-Fe-Cl plane that controls either the Cl- or the OH- to rebound depending on the relative π-overlap with the substrate C radical. The differential contribution of the two FMOs to chlorination versus hydroxylation selectivity in SyrB2 is related to a reaction mechanism that involves two asynchronous transfers: electron transfer from the substrate radical to the iron center followed by late ligand (Cl- or OH-) transfer to the substrate.
Keywords: halogenace; molekulární konformace; Nonheme Iron Proteins; termodynamika; Molecular Conformation; Quantum Theory; kvantová teorie; Hydroxylation; Halogenation; Thermodynamics; nehemové proteiny obsahující železo; hydroxylace